ARTICULATING STATUS IN ANCIENT GREECE: STATUS (IN)CONSISTENCY AS A NEW APPROACH. (31st January 2017) - Davies, P. A.
Abstract : Current descriptions of social status in the Greek world are strongly influenced by the works of Moses I. Finley and G. E. M. de Ste. Croix, whose models were grounded in the sociologies of Weber and Marx. This article outlines a new paradigm for social status based on a model from the social sciences, commonly described as status (in)consistency. The article demonstrates the descriptive and interpretive usefulness of this approach using two case studies: social status and social mobility in classical Lakedaimonian society; and the lives and status of Pasion of Acharnai and his son Apollodoros.